Effect of Media on Acetone-Butanol-Ethanol Fermentation by Isolated Clostridium spp. - Budsaba Buakhiaw; Vorapat Sanguanchaipaiwong (My University, 2017)
Butanol is one of the important industrial chemicals and currently recognized as an alternative and renewable biofuel. It has been receiving an increased attention due to the energy crisis and the decrease of petroleum. Butanol can be obtained from several anaerobic microorganisms, which belong to genus Clostridium. The problem is the ability of Clostridium sp. to produce low concentration of butanol. Consequently, the screening and isolating for new Clostridium strains which can produce high amount of biobutanol has been required. Clostridium sp. strain G10 was isolated from marsh sediment in King Mongkut's Institute of Technology Ladkrabang (KMITL), Bangkok, Thailand. Its capability of butanol production was 5.89 g/L with a total acetone-butanol-ethanol (ABE) concentration of 8.48 g/L under anaerobic conditions. The medium composition significantly affected the performance of (ABE) production by strain G10. To investigate the effect of media on solvent production by isolated strain, four media, including RCM, T6, GYCC, and P2 medium (30 g/L glucose in each medium) were utilized to cultivate Clostridium sp. strain G10. The results revealed that, T6 medium could produce the highest biobutanol concentration (13.49 g/L) and ABE was 16.22 g/L (acetone 2.63 g/L and ethanol 0.10 g/L).
Keywords: Clostridium acetobutylicum; Biofuel production and bioconversion